Pengaruh Rasio Keuangan Bank Terhadap Profitabilitas Bank Umum Non-Devisa - I Made Hegar Danendra Nararya; Daffa Sukma Falih; Farhan Taufiqurrahman; Ladi Wajuba Perdini Fisabilillah; Tony Seno Aji (Jurnal Ekonomika : INDEPENDEN, 2025)
Profitability is one of the most appropriate indicators to measure the financial performance of a bank. This study aims to analyze the effect of bank financial ratios on profitability in non-foreign exchange commercial banks for the 2019-2023 period. The sample of this research is 4 (four) non-foreign exchange commercial banks in Indonesia, with the data analysis method used, namely the panel data regression model with the Fixed Effect Model (FEM) approach. The results showed that the financial ratio NIM has a significant influence and has a positive direction on bank ROA. BOPO financial ratio has a significant influence and has a negative direction on bank ROA. CAR financial ratio has an insignificant influence and has a positive direction on bank ROA.